Choice with delayed and probabilistic reinforcers: Effects of prereinforcer and postreinforcer stimuli - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1998)
In Experiment 1, pigeons' pecks on a green key led to a 5-s delay with green houselights, and then food was delivered on 20% (or, in other conditions, 50%) of the trials. Pecks on a red key led to an adjusting delay with red houselights, and then food was delivered on every trial. The adjusting delay was used to estimate indifference points: delays at which the two alternatives were chosen about equally often. Varying the presence or absence of green houselights during the delays that preceded possible food deliveries had large effects on choice. In contrast, varying the presence of the gr een or red houselights in the intertrial intervals had no effects on choice. In Experiment 2, pecks on the green key led to delays of either 5 s or 30 s with green houselights, and then food was delivered on 20% of the trials. Varying the duration of the green houselights on nonreinforced trials had no effect on choice. The results suggest that the green houselights served as a conditioned reinforcer at some rimes but not at others, depending on whether or nor there was a possibility that a primary reinforcer might be delivered. Given this interpretation of what constitutes a conditioned reinforcer, most of the results were consistent with the view that the strength of a conditioned reinforcer is inversely related to its duration.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-649-994-407-690 tex.type: [object Object]
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning; Psychological/ph [Physiology]; *Reinforcement; Psychology; Animals; Behavior; Animal; Behavior; Animal/ph [Physiology]; Choice; Choice Behavior; Columbidae; Conditioned reinforcement; Conditioning (Psychology); Delay; Key peck; Pigeons; Probability; Reinforcement (Psychology); Time Factors; animal; animal behavior; article; comparative study; conditioning; decision making; dept.psy; physiology; pigeons and doves; reinforcement; time